2012
DOI: 10.1038/modpathol.2012.59
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cold ischemic time on the immunohistochemical evaluation of estrogen receptor, progesterone receptor, and HER2 expression in invasive breast carcinoma

Abstract: The American Society of Clinical Oncology/College of American Pathologist (ASCO/CAP) guidelines on breast cancer currently recommend a cold ischemic time of o1 h, although data are limited. Breast resection specimens were subjected to variable cold ischemic time periods (0.5, 1, 2, 3, 4, 24, and 48 h) within the refrigerator and at room temperature. The study included 25 tumors, all of which had refrigerated samples. Nonrefrigerated samples (samples at room temperature) were present on 23 cases. Hormone recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
94
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(98 citation statements)
references
References 28 publications
4
94
0
Order By: Relevance
“…Our comprehensive proteome analysis, which greatly expands on prior studies of the consequences of cold ischemia on protein expression (15,16), revealed that none of the Ͼ10,000 proteins detected and quantified changed in abundance as a result of cold ischemia in a time span of up to one hour post-excision. However, because of the inability of conventional "bottom-up" MSbased proteomics technology to analyze the integrity of intact proteins (as samples are digested to peptides prior to analysis), we cannot exclude the possibility that limited proteolysis such as apoptotic regulation by caspases occurs at early time points of cold ischemia.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Our comprehensive proteome analysis, which greatly expands on prior studies of the consequences of cold ischemia on protein expression (15,16), revealed that none of the Ͼ10,000 proteins detected and quantified changed in abundance as a result of cold ischemia in a time span of up to one hour post-excision. However, because of the inability of conventional "bottom-up" MSbased proteomics technology to analyze the integrity of intact proteins (as samples are digested to peptides prior to analysis), we cannot exclude the possibility that limited proteolysis such as apoptotic regulation by caspases occurs at early time points of cold ischemia.…”
Section: Discussionmentioning
confidence: 81%
“…A study employing AQUA, a quantitative immunofluorescence technique, found slightly increased expression of hypoxia inducible factor but no changes in protein abundance in the four breast cancer biomarker proteins ER, PR, HER2, and Ki67 over a time span of up to 7 h, though signal reduction occurred in a subset of samples at longer intervals of up to 48 h of cold ischemia (15). In another study employing immunohistochemistry, the breast cancer biomarker proteins ER, PR, and Her2 were found to be stable for up to 2 h at room temperature (16). Evidence from RPPA studies evaluating the time course of changes induced by cold ischemia has shown that even when the total protein levels and levels of many phosphoproteins are constant, the phosphorylation stoichiometry of specific proteins can change, in some cases significantly (9,17).…”
mentioning
confidence: 99%
“…32 In light of these concerns, several quality assurance programs have been created including ad hoc consensus conference recommendations, 33,34 and the guideline recommendations from the American Society of Clinical Oncology/College of American Pathologist for HER-2, ER, and PR testing, 35,36 which includes mandatory proficiency testing. These national efforts have led to marked improvements in the quality, reliability, and inter-laboratory agreement for these breast cancer assays, [37][38][39][40][41] and have made the use of semiquantitative immunohistochemistry results more feasible for estimating risk. These efforts in improving quality may be most helpful in reconsidering the role of Ki-67 as part of the routine panel for testing of breast cancers.…”
Section: Modern Pathology (2015) 28 921-931mentioning
confidence: 99%
“…Ready-to-use assays offer improved reproducibility and consistency, minimizing effects arising from reagent diversity, as well as variability that can arise from antigen retrieval. [8][9][10][11][12][13][14][15][16] Surprisingly, these platform-specific ready-to-use assays have never been directly compared using the same clinical outcome series.…”
mentioning
confidence: 99%